Myomectomy scar ectopic pregnancy: diagnostic challenges and management conundrum: a case report - Kandaswami, Dhanabagyam; Jayapal, Kavitha; Sudhakar, Pradeepa; Usman, Shyla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Two patients with a history of previous myomectomy came to the centre for infertility evaluation. Both underwent controlled ovarian stimulation followed by ICSI at our centre. Frozen embryo transfer was done with hormone replacement therapy protocol where two good quality blastocysts were transferred on day 5. After embryo transfer, urine pregnancy tests were positive. But early scans showed pregnancies implanted in the previous scar sites. Laparoscopic removal of the gestational sac was done under ultrasound guidance. This rare form of ectopic pregnancy could occur when the embryo implantation occurs under the serosa at the site of suture failure from the previous surgery. Laparascopic enucleation is the best form of treatment in such cases.